Optimalisasi Pemberdayaan Masyarakat Dalam Peningkatan SDM Serta Pemanfaatan Sarana dan Prasarana Desa Kedungsari Melalui Pendidikan Berbasis Literasi - Ragil Ira Mayasari; Nouval Nandra Dzakim; Bagus Oktavianto; Mochammad Surya Rahman Dani; Bunga Aldama Arthavianto; Zaidatuzulfa Zaidatuzulfa; Andy Kurniawan; Mukhamad Arif Prasetiya; Marsella Putri; Dharma Priti Sri Lestari; Andini Widyaningrum; Shinta Dwinanda; Anisa Vindi Rahmawati; Ela Wulandari; Mohammad Ali Fikri Zamzami; Mochamad Rizal Yogaswara; Vindy Permata Sari; Istifadatin Nadliroh; Aulia Amirotus Sholikhah; Galih Meydamara; Bismo Arsha Ardana Desponsa; Puri Rahayu; Friesca Aulia Putri Ardina; Nova Istyadola Rahmadhani (Jurnal Masyarakat Mengabdi Nusantara, 2025)
The optimization of community empowerment is a strategic step in improving the quality of human resources (HR) in Kedungsari Village. This community service aims to implement literacy-based education as a means of empowering the community by utilizing existing village facilities and infrastructure. Through a participatory approach, the community is involved in various socialization and training activities relevant to local needs to enhance their skills, awareness, and knowledge. The results of the program indicate that literacy-based education not only improves reading and writing skills but also strengthens the community’s understanding of the importance of maintaining environmental cleanliness, social values, and managing local potentials to support village development. The utilization of facilities such as the village library and community hall is key to the program's success. With a targeted and collaborative implementation, this program is expected to enhance the quality of life of Kedungsari Village residents in social, economic, and environmental aspects. In conclusion, sustained support from universities, village governments, and local communities is necessary to create an inclusive, competitive, and sustainable empowerment ecosystem.